1996
DOI: 10.3354/meps138209
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of inducible defense and resource availability on phlorotannins in the North Atlantic brown alga Fucus vesiculosus

Abstract: Research seeking to explain the ecological role of polyphenolics (phlorotannins) in plants and brown algae has largely focused on 2 alternative concepts, the carbonhutrient (Cm) balance and the inducible defense models. We tested the hierarchy of effects of both models on phlorotannin production in the brown alga Fucus veslculosus (Fucales) by simultaneously manipulating the N environment and simulating herbivory for 2 oceanic (high and low intertidal) and estuarine populations. We measured phlorotannin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 30 publications
7
104
1
Order By: Relevance
“…For example, induced behavioral responses in organisms, such as diel vertical migrations [4], will affect the transport and cycling of carbon and nutrients in aquatic systems. A more complex case is posed by feedbacks between nutrient availability and inducible defenses in terrestrial plants and marine algae: in these situations, carbon and nutrient availability affects the expression of inducible defenses, which in turn alter carbon and nitrogen balance through interspecific effects [58]. Exciting new avenues for research include the effects of plasticity on community diversity, resilience, zonation and patchiness, as well as rates of energy transfer throughout ecosystems and ecosystem functioning [52].…”
Section: Reviewmentioning
confidence: 99%
“…For example, induced behavioral responses in organisms, such as diel vertical migrations [4], will affect the transport and cycling of carbon and nutrients in aquatic systems. A more complex case is posed by feedbacks between nutrient availability and inducible defenses in terrestrial plants and marine algae: in these situations, carbon and nutrient availability affects the expression of inducible defenses, which in turn alter carbon and nitrogen balance through interspecific effects [58]. Exciting new avenues for research include the effects of plasticity on community diversity, resilience, zonation and patchiness, as well as rates of energy transfer throughout ecosystems and ecosystem functioning [52].…”
Section: Reviewmentioning
confidence: 99%
“…' Phlorotannin induction can occur rapidly, within 1-3 days of wounding. 111 ' 145 Pavia and Toth 147 found that a few weeks of grazing by the periwinkle snail Littorina obtusata could induce the production of phlorotannins in Ascophyllum nodosum, but grazing by the isopod Idotea granulosa and simulated herbivory caused no significant changes in phlorotannin levels. They proposed that patterns of grazing by L. obtusata, which lives and feeds on a few species of fucoid algae, could be an important factor in explaining natural variation in the levels of phlorotannins in A. nodosum.…”
Section: Macroalgaementioning
confidence: 99%
“…They are suggested to have multiple ecological roles: some phlorotannins act as chemical defenses against herbivory (e.g., Steinberg, 1988;Targett and Arnold, 1998;Arnold and Targett, 2000;Pavia and Toth, 2000a) and as antifouling substances (Sieburth and Conover, 1965;Wikström and Pavia, 2004), although the evidence for this function is equivocal (Jennings and Steinberg, 1997). Concentrations of phlorotannins show phenotypic plasticity in response to environmental parameters, such as salinity, nutrient and light availability, ultraviolet irradiation, and intensity of herbivory (Yates and Peckol, 1993;Peckol et al, 1996;Pavia et al, 1997;Pavia and Toth, 2000b;Honkanen et al, 2002;Swanson and Druehl, 2002). This implies that the pools of soluble phlorotannins are not stable but rather in a state of flux, and their concentration may be determined by the balance between rates of synthesis and turnover (Arnold and Targett, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Resource-based hypotheses assume that under conditions of good nutrient availability, the allocation of carbon will shift from the production of secondary metabolites to growth (e.g., Bryant et al, 1983;Herms and Mattson, 1992). Often, negative correlations have been found between the contents of available nutrients and the production of soluble phenolic compounds, both in terrestrial plants (reviewed by Herms and Mattson, 1992) and brown algae, although much spatial and temporal variation in this relationship exists (e.g., Yates and Peckol, 1993;Steinberg, 1995;Peckol et al, 1996;Pavia and Toth, 2000b). Variation in the contents of soluble phlorotannins has also been found among different parts of algae.…”
Section: Introductionmentioning
confidence: 99%